Matt polyester film and preparation method thereof
Low light transmission was prepared by using a mixture of modified serpentine and polyethylene terephthalate as the first filler in a matte polyester film, combining black pigment, kaolin, barium sulfate and silane coupling agent. The matte polyester film with excellent mechanical properties and antibacterial properties solves the problem of difficult to take into account both mechanical strength and light transmittance in the prior art, reduces production costs and reduces environmental pollution.
Patent Information
- Application Number
- CN202510019673.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2045-01-07
AI Technical Summary
While improving haze and low gloss, existing matte polyester films are difficult to take into account both mechanical strength and light transmittance, and the preparation process is complicated, the cost is high, and the environmental pollution is serious.
Using a mixture of modified serpentine and polyethylene terephthalate as the first filler, combined with black pigment, kaolin, barium sulfate and silane coupling agent, matte polyester with black absorbing layer and white surface layer is prepared. film. In this way, the film is enhanced to enhance its adhesiveness and occlusion, reduce light transmittance, and impart antibacterial properties.
Polyester films with low light transmittance, excellent mechanical properties and antibacterial properties have been achieved, which reduces production costs, reduces environmental pollution, and broadens the application fields of polyester films.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the field of polyester films, and in particular to a matte polyester film and a preparation method thereof. Background Art
[0002] Matt polyester film has a wide range of applications in many fields due to its unique optical and physical properties. This film is mainly used in heat transfer film, hot stamping film, hot cloth, leather, transfer paper, decorative sheet profiles, aluminum-plated color printing packaging, signs and other products. According to different glossiness, matte polyester film can be divided into three categories: low matt, medium matt and high matt. Among them, high matt products are particularly suitable for high-end cosmetic packaging, high-end decorative sheet profiles, transfer cigarette pack lining paper, hot leather, hot cloth and other transfer products because their haze is greater than 95% and gloss is less than 17%. These products usually require the pattern surface to have a very low gloss, or even no gloss.
[0003] At present, the research on matte polyester film mainly focuses on improving its performance through copolymerization modification and inorganic filler modification. Although the copolymerization modification method can meet the requirements of high haze and mechanical properties, its development is limited due to its complex process and high cost. Therefore, the industry generally adopts inorganic filler modification to improve the matte degree of PET film. Researchers improve the matte effect of PET film by adding different types of inorganic fillers, such as nano-silica, kaolin and barium sulfate. While improving the matte effect, these studies are also exploring how to maintain or improve the mechanical strength and light transmittance of the film.
[0004] Although some progress has been made in existing research, matte polyester film still has some shortcomings and needs further improvement. For example, increasing the additive content to achieve the effect of high haze and low gloss may make the additive difficult to disperse and have poor interfacial compatibility with polyester, thereby reducing the mechanical strength of the polyester film. In addition, the effective content of the matting agent in existing preparation methods such as the in-situ polymerization method is limited by the process, and the prepared polyester matte film has a high gloss and can only be used to produce ordinary polyester matte film. In order to obtain a high-matte polyester film, it is usually necessary to perform an additional coating treatment process on the surface of the film, which not only increases the cost, but also may cause pollution to the environment. Therefore, future research needs to explore more efficient inorganic filler dispersion technology and develop new preparation methods to improve the performance of matte polyester film and reduce production costs while reducing the impact on the environment. Summary of the invention
[0005] The purpose of the present application is to provide a polyester film with low light transmittance, good mechanical properties and certain antibacterial properties.
[0006] In order to achieve the above objectives, the technical solution adopted in the present application is: to provide a matte polyester film, including two upper and lower white surface layers, and a black light-absorbing layer arranged between the white surface layers, the raw materials for preparing the black light-absorbing layer include a first filler, and the first filler is a mixture of modified serpentine and polyethylene terephthalate.
[0007] As a preference, the modified serpentine and the polyethylene terephthalate are mixed in a mass ratio of (1:1) to (1:5) to obtain the first filler.
[0008] As another preference, the particle size of the modified serpentine is 100-200 nm, and the particle size of the polyethylene terephthalate is 400-500 nm.
[0009] As another preferred embodiment, the raw materials for preparing the modified serpentine include: copper formate, serpentine, saturated fatty acid, silane coupling agent and solution.
[0010] As another preferred embodiment, the preparation method of the modified serpentine is as follows: dissolving copper formate and adding serpentine powder and saturated fatty acid, reacting at elevated temperature and pressure, then concentrating the solution under reduced pressure to obtain a reactant, calcining the reactant in an oxygen atmosphere and a vacuum atmosphere in turn, grinding it into powder and mixing it with ethanol, then adding a silane coupling agent to react for a period of time, concentrating under reduced pressure and drying to obtain the modified serpentine.
[0011] As another preference, the raw materials for preparing the black light-absorbing layer further include: black pigment, kaolin, barium sulfate, silane coupling agent and PET masterbatch.
[0012] As another preferred embodiment, the raw materials for preparing the white surface layer include: polyacrylonitrile, glass fiber, lignin, the first filler, talcum powder, calcium carbonate, alumina ceramic powder and PET masterbatch.
[0013] The present application also provides a method for preparing a matte polyester film, comprising the following preparation steps: S1: dissolving copper formate and adding serpentine powder and saturated fatty acid, reacting at elevated temperature and pressure, and then concentrating the solution under reduced pressure to obtain a reactant, calcining the reactant in an oxygen atmosphere and a vacuum atmosphere in turn, grinding it into powder and mixing it with ethanol, then adding a silane coupling agent to react for a period of time, concentrating it under reduced pressure and drying it to obtain a modified serpentine; S2: grinding the modified serpentine and polyethylene terephthalate into powders respectively and mixing them to prepare a first filler ; The first filler, black pigment, kaolin, barium sulfate, silane coupling agent and PET masterbatch are mixed and extruded through a twin-screw extruder to obtain a black light-absorbing layer; S3: Grind polyacrylonitrile, glass fiber and lignin into powder, then add the first filler, talcum powder, calcium carbonate powder, alumina ceramic and PET masterbatch, mix and extrude through a twin-screw extruder to obtain a white surface layer; The white surface layer is arranged on both sides of the black light-absorbing layer, and the three-layer film is heated, melted and extruded in a casting machine, and the matte polyester film is obtained after stretching and shaping.
[0014] As another preferred embodiment, in the step S1, the reactant is calcined at 600-630° C. for 2-3 h in an oxygen atmosphere, and then transferred to a vacuum furnace and calcined at 850-880° C. for 50-80 min to obtain a calcined product.
[0015] More preferably, the calcined product is mixed with ethanol in a mass ratio of 2:(55-59).
[0016] Compared with the prior art, the beneficial effects of this application are: (1) In the present application, a first filler is added to the raw material for preparing the black light-absorbing layer, so that the adhesion between the layers of the matte polyester film obtained is improved, the bite force of the overall film layer is enhanced, and the film has a lower light transmittance; (2) Kaolin and silane coupling agent are added to the raw materials for preparing the black light-absorbing layer of the present application, so that other filler particles are distributed more evenly and the light-absorbing effect of black is enhanced; (3) The white surface layer of the present application utilizes glass fibers to form a polyester network structure, and promotes the fusion of glass fibers and polyester through the multi-branch characteristics of lignin, forming a film layer with a dense structure and uniform grafting structure, which has better rigidity. DETAILED DESCRIPTION
[0017] Below, the present application is further described in conjunction with specific implementation methods. It should be noted that, under the premise of no conflict, the various embodiments or technical features described below can be arbitrarily combined to form new embodiments.
[0018] The terms "including" and "having" and any variations thereof in the specification and claims of this application are intended to cover non-exclusive inclusions. For example, a process, method, system, product or apparatus comprising a series of steps or units is not necessarily limited to those steps or units explicitly listed, but may include other steps or units not explicitly listed or inherent to these processes, methods, products or apparatuses.
[0019] The matte polyester film of the present application comprises a double-layer white surface layer and a black light-absorbing layer between the white surface layers. The raw materials for preparing the black light-absorbing layer comprise a first filler, which is a mixture of modified serpentine and polyethylene terephthalate.
[0020] In the present application, a first filler is added to the raw materials for preparing the black light-absorbing layer, so that the adhesion between the layers of the matte polyester film obtained is improved, the bite force of the overall film layer is enhanced, the light transmittance is lowered, and additionally, certain antibacterial properties are possessed.
[0021] In some embodiments, the raw materials for preparing the modified serpentine include: copper formate, serpentine, saturated fatty acid, silane coupling agent, ethanol and solution.
[0022] Serpentine is a general term for a hydrous magnesium-rich silicate mineral, including antigorite, lizardite, chrysotile, etc. Their colors are usually green, but there are also light gray, white or yellow. Serpentine is named because of its grayish white and stone red net pattern, which resembles snake skin. The structure of serpentine is often curled, like fiber, and such serpentine is often used as asbestos. Block or fibrous serpentine has a luster, block like wax, fibrous like silk.
[0023] Serpentine is added to polyester film. Serpentine has high chemical activity. There are unsaturated Si-O-Si, O-Si-O, magnesium bonds, OH- and other active groups in its fracture structure, which can enhance the chemical stability of PET film.
[0024] Serpentine has low hardness, high temperature resistance of 550-700℃, stable properties, strong adsorption, good wear resistance and low friction coefficient. These characteristics make serpentine useful in the preparation of lubricating self-repairing agents, and adding it to PET film may improve the wear resistance and friction reduction properties of the film.
[0025] Serpentine can be used to prepare environmental materials that adsorb harmful anions, heavy metal ions and some organic matter. Therefore, the addition of serpentine may make PET film have environmental purification function. In addition, the addition of serpentine to PET film may improve the heat resistance of the film.
[0026] In some embodiments, a method for preparing modified serpentine is provided: copper formate is dissolved in a solvent, serpentine powder and saturated fatty acids are added, the temperature and pressure are increased to react for a period of time, and then the reactants are concentrated under reduced pressure to obtain reactants, the reactants are calcined in an oxygen atmosphere, ground into powder and mixed with ethanol, and then a silane coupling agent is added to react for a period of time, and the reactants are concentrated under reduced pressure and dried to obtain modified serpentine.
[0027] The present application improves the film strength and biological resistance by making modified serpentine powder. Copper formate is mixed and dissolved with ultrapure water, serpentine powder is added for adsorption, saturated fatty acids are added, and the mixed solution is used to promote the movement of serpentine powder under the action of boiling solution, fully adsorbing copper formate, and at the same time, the temperature is increased, and the high boiling point of saturated fatty acids is used to promote the temperature rise of the mixed solution, and copper ions are formed in the mixed solution to achieve the purpose of serpentine loading copper; after drying, multiple high-temperature treatments are performed to convert the copper in the serpentine into copper oxide, and then a silane coupling agent is added to improve the fusion effect of the modified serpentine in polyester. The friction of the prepared film layer is large, the bonding effect is higher when the multilayer film is combined to form a composite film, the overall film layer has a strong bite force, and has a higher film use strength.
[0028] Moreover, after serpentine is loaded with copper oxide, the active copper oxide ions on the surface of nano-copper oxide can interact with the cell membrane of bacteria or fungi, destroying their cell structure and function, and then inhibiting their growth and reproduction. This antibacterial mechanism makes nano-copper oxide have strong antibacterial activity against a variety of pathogenic microorganisms, making it difficult for microorganisms to attach and reproduce on the film layer in a complex environment, ensuring the cleanliness of the film layer, and making the polyester film have certain antibacterial properties.
[0029] In some preferred embodiments, the saturated fatty acid is a carbon chain containing 15 to 17 carbon atoms in the molecular formula, such as pentadecanoic acid, hexadecanoic acid or heptadecanoic acid.
[0030] In some preferred embodiments, the silane coupling agent is KH550 or KH570.
[0031] In some embodiments, the present application also provides a method for preparing a first filler: grinding modified serpentine and polyethylene terephthalate into powder, and mixing the modified serpentine powder and the polyethylene terephthalate powder to obtain a first filler.
[0032] In some preferred embodiments, the modified serpentine powder and the polyethylene terephthalate powder are mixed in a mass ratio of (1:1) to (1:5) to obtain the first filler.
[0033] In some embodiments, the modified serpentine is ground into a powder of 100-200 nm, and the polyethylene terephthalate is ground into a powder of 400-500 nm.
[0034] In some embodiments, the raw materials for preparing the black light absorbing layer of the present application include: a first filler, a black pigment, kaolin, barium sulfate, a silane coupling agent and a PET masterbatch.
[0035] Kaolin is added to the black light-absorbing layer, and the polyester molecular chains are accommodated by the layered structure of kaolin, which strengthens the adsorption of barium sulfate and black pigment. After adding silane coupling agent for grafting, the filler particles in the film layer are more evenly distributed, and the light-absorbing effect of black is enhanced. In particular, the temperature of the film layer rises after light absorption. The blocking of kaolin and barium sulfate can ensure the high-temperature stability of the film layer, ensuring better structural strength during use.
[0036] In some embodiments, the raw materials for preparing the white surface layer also include a first filler.
[0037] In some embodiments, the raw materials for preparing the white surface layer of the present application include: polyacrylonitrile, glass fiber, lignin, a first filler, talcum powder, calcium carbonate, alumina ceramic powder and PET masterbatch.
[0038] In the white surface layer, polyacrylonitrile, glass fiber and lignin are mixed, and the high melting point of polyacrylonitrile is used to promote the adhesion of glass fiber and lignin to improve the high-temperature supporting performance of the membrane layer. The glass fiber is used to form a network structure of polyester, and the multi-branch characteristics of lignin are used to promote the fusion of glass fiber and polyester, forming a membrane layer with a dense structure and uniform grafting structure, which has better rigidity.
[0039] In some embodiments, the present application also provides a method for preparing a matte polyester film: a black light-absorbing layer is placed between a double-layer white surface layer, the three-layer material is heated, melted, extruded, stretched and shaped into a film in a casting machine to produce the matte polyester film of the present application.
[0040] The present application also provides a method for preparing a matte polyester film, comprising the following preparation steps: S1: dissolving copper formate and adding serpentine powder and saturated fatty acid, reacting at elevated temperature and pressure, then concentrating the solution under reduced pressure to obtain a reactant, calcining the reactant in an oxygen atmosphere and a vacuum atmosphere in turn, grinding the reactant into powder and mixing it with ethanol, then adding a silane coupling agent to react for a period of time, concentrating under reduced pressure and drying to obtain a modified serpentine; S2: Grinding modified serpentine and polyethylene terephthalate into powders respectively and mixing them to prepare a first filler; mixing the first filler, black pigment, kaolin, barium sulfate, silane coupling agent and PET masterbatch and extruding them through a twin-screw extruder to obtain a black light-absorbing layer; S3: Grind polyacrylonitrile, glass fiber, and lignin into powder, add the first filler, talcum powder, calcium carbonate powder, alumina ceramics, and PET masterbatch, mix, and extrude through a twin-screw extruder to obtain a white surface layer; White surface layers are arranged on both sides of the black light-absorbing layer, and the three-layer film is heated, melted and extruded in a casting machine, and a matte polyester film is obtained after stretching and shaping.
[0041] Example 1 A matte polyester film is prepared, comprising the following preparation steps: S1: By mass, 1 part of copper formate was mixed with 20 parts of ultrapure water, 13 parts of serpentine powder with a particle size of 100 nm was added, the solution was heated to 30 °C and stirred for reaction for 50 min, 40 parts of 15-carbon saturated fatty acid were added, and the pressure was increased so that the container maintained about 1.3 standard atmospheric pressure, the solution was heated to boiling and continued for 15 min, and then the solution was concentrated under reduced pressure at room temperature and pressure to obtain a reactant; The reactants were placed in a calcining furnace and calcined at 600 °C for 2 h in an oxygen atmosphere, and then transferred to a vacuum furnace and calcined at 850 °C for 50 min. The calcined product was placed in a ball mill and ground for 2 h. The powder was mixed with ethanol at a mass ratio of 2:55, and 6% of the mass fraction of silane coupling agent KH550 was added to the mixed powder. The mixture was ultrasonically shaken for 40 min, and the solution was concentrated under reduced pressure and dried to obtain modified serpentine. S2: Grinding the modified serpentine into a powder of 100 nm in a grinder, grinding the polyethylene terephthalate into a powder of 400 nm in a grinder, and mixing the two powders in a ratio of 1:2 to prepare a first filler; By weight, 80 parts of the first filler, 15 parts of carbon black, 5 parts of kaolin, 3 parts of barium sulfate, 1 part of KH550 silane coupling and 200 parts of PET masterbatch were mixed for 30 minutes and extruded by a twin-screw extruder at 260°C to obtain a black light-absorbing layer; S3: By weight, 10 parts of polyacrylonitrile, 1 part of glass fiber, and 1 part of lignin raw material were mixed into a grinder and ground into a powder of 300 nm, and then 110 parts of the first filler, 15 parts of talc, 10 parts of calcium carbonate powder, 8 parts of alumina ceramics, and 200 parts of PET masterbatch were added. The materials were mixed and stirred for 30 minutes, and then heated to 280 °C and extruded in a twin-screw extruder to obtain a white surface layer; The matte polyester film of the present application is prepared by using a black light-absorbing layer as the core material, white surface layers as the upper and lower surface layers, the black light-absorbing layer being sandwiched between the two white surface layers, the mass ratio of the black light-absorbing layer to the white surface layer being 3:1, and being heated, melted and extruded in a casting machine, and stretched and shaped into a film at 90-93°C.
[0042] Example 2 A matte polyester film is prepared, comprising the following preparation steps: S1: By weight, 5 parts of copper formate and 30 parts of ultrapure water were mixed, 15 parts of serpentine powder with a particle size of 150 nm were added, the solution was heated to 35 °C and stirred for reaction for 70 min, 50 parts of 17-carbon saturated fatty acid were added, and the pressure was increased so that the container maintained about 1.5 standard atmospheric pressure, the solution was heated to boiling and continued for 18 min, and then the solution was concentrated under reduced pressure at room temperature and pressure to obtain the reactant; The reactants were placed in a calcining furnace and calcined at 630 °C for 3 h in an oxygen atmosphere, and then transferred to a vacuum furnace and calcined at 880 °C for 80 min. The calcined product was placed in a ball mill and ground for 4 h. The powder was mixed with ethanol at a mass ratio of 2:59, and 7% of the mass fraction of silane coupling agent KH550 was added to the mixed powder. Ultrasonic vibration was performed for 45 min, and the solution was concentrated under reduced pressure and dried to obtain modified serpentine. S2: Grinding the modified serpentine into a powder of 200 nm in a grinder, grinding the polyethylene terephthalate into a powder of 500 nm in a grinder, and mixing the two powders in a ratio of 1:1 to prepare a first filler; By weight, 90 parts of the first filler, 18 parts of carbon black, 8 parts of kaolin, 5 parts of barium sulfate, 2 parts of KH570 silane coupling and 200 parts of PET masterbatch were mixed for 30 minutes and extruded by a twin-screw extruder at 275°C to obtain a black light-absorbing layer; S3: By weight, 15 parts of polyacrylonitrile, 3 parts of glass fiber, and 2 parts of lignin raw materials were mixed into a grinder and ground into a powder of 400 nm, and then 120 parts of the first filler, 19 parts of talc, 13 parts of calcium carbonate powder, 11 parts of alumina ceramics, and 200 parts of PET masterbatch were added. The materials were mixed and stirred for 37 minutes, and then heated to 295 °C and extruded in a twin-screw extruder to obtain a white surface layer; The matte polyester film of the present application is prepared by using a black light-absorbing layer as the core material, white surface layers as the upper and lower surface layers, the black light-absorbing layer being sandwiched between the two white surface layers, the mass ratio of the black light-absorbing layer to the white surface layer being 3:1.4, heating and melt-extruding in a casting machine, and stretching and shaping into a film at 90-93°C.
[0043] Example 3 A matte polyester film is prepared, comprising the following preparation steps: S1: By weight, 3 parts of copper formate and 25 parts of ultrapure water were mixed, 15 parts of serpentine powder with a particle size of 150 nm were added, the solution was heated to 33 °C and stirred for 70 min, 40 parts of 17-carbon saturated fatty acid were added, and the pressure was increased so that the container maintained about 1.5 standard atmospheric pressure, the solution was heated to boiling and continued for 18 min, and then the solution was concentrated under reduced pressure at room temperature and pressure to obtain the reactant; The reactants were placed in a calcining furnace and calcined at 630 °C for 3 h in an oxygen atmosphere, and then transferred to a vacuum furnace and calcined at 880 °C for 80 min. The calcined product was placed in a ball mill and ground for 4 h. The powder was mixed with ethanol at a mass ratio of 2:59, and 7% of the mass fraction of silane coupling agent KH550 was added to the mixed powder. The mixture was ultrasonically shaken for 40 min, and the solution was concentrated under reduced pressure and dried to obtain modified serpentine. S2: Grinding the modified serpentine into a powder of 200 nm in a grinder, grinding the polyethylene terephthalate into a powder of 500 nm in a grinder, and mixing the two powders in a ratio of 1:5 to prepare a first filler; By weight, 90 parts of the first filler, 15 parts of carbon black, 8 parts of kaolin, 3 parts of barium sulfate, 2 parts of KH570 silane coupling and 200 parts of PET masterbatch were mixed for 45 minutes and extruded by a twin-screw extruder at 275°C to obtain a black light-absorbing layer; S3: By weight, 15 parts of polyacrylonitrile, 1 part of glass fiber, and 2 parts of lignin raw materials were mixed into a grinder and ground into a powder of 400 nm, and then 110 parts of the first filler, 19 parts of talc, 10 parts of calcium carbonate powder, 11 parts of alumina ceramics, and 200 parts of PET masterbatch were added. The materials were mixed and stirred for 37 minutes, and then heated to 280 °C and extruded in a twin-screw extruder to obtain a white surface layer; The matte polyester film of the present application is prepared by using a black light-absorbing layer as the core material, white surface layers as the upper and lower surface layers, the black light-absorbing layer being sandwiched between the two white surface layers, the mass ratio of the black light-absorbing layer to the white surface layer being 3:1, and being heated, melted and extruded in a casting machine, and stretched and shaped into a film at 90-93°C.
[0044] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that, in the process of preparing the modified serpentine in step S1, no saturated fatty acid is added, and the other preparation steps are consistent with the preparation steps in Example 1 to obtain the polyester film of Comparative Example 1.
[0045] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that, in the process of preparing the modified serpentine in step S1, the step of calcining under an oxygen atmosphere is removed, and the reactants are directly transferred to a vacuum furnace and calcined for 4 hours. The other preparation steps are consistent with the preparation steps in Example 1 to obtain the polyester film of Comparative Example 2.
[0046] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that the first filler is not added to the black light absorbing layer and the white surface layer, and the other preparation steps are consistent with the preparation steps in Example 1, so as to prepare the polyester film of Comparative Example 3.
[0047] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that serpentine is used instead of the first filler and added to the raw materials for preparing the white surface layer and the black light-absorbing layer, and the other preparation steps are consistent with the preparation steps in Example 1 to obtain the polyester film of Comparative Example 4.
[0048] Performance Testing 1. The tensile strength of each embodiment and each comparative example was tested with reference to GB / T 1040.3 “Determination of tensile properties of plastics Part 3: Test conditions for films and sheets”.
[0049] 2. The transmittance of each embodiment and each comparative example was tested using an ultraviolet-visible spectrophotometer.
[0050] 3. Antibacterial rate test: Taking Escherichia coli as an example, the basement membrane is cut into pieces and placed at the bottom of the wells of a 24-well plate. Subsequently, 100 μL of the diluted bacterial suspension (about 105 CFU / mL) is dripped into each well and evenly dispersed on the surface of the membrane. The 24-well plate is then placed in a bacterial incubator and incubated at 37°C for 6 hours. Each sample is then taken out and soaked in a test tube containing 10 mL of PBS solution, and all test tubes are then placed in a water bath thermostat oscillator (150 rpm) and shaken for 10 minutes. Subsequently, 60 μL of the diluted bacterial suspension is spread on a nutrient agar plate, incubated at 37°C for 24 h, and the number of live colonies is counted, and the experiment is repeated three times.
[0051] The above performance test results are recorded in Table 1 below.
[0052] Table 1 Performance test results of various embodiments and comparative examples
[0053] Analysis of the performance test results of each embodiment and each comparative example shows that the matte polyester film prepared in the present application has low light transmittance, good mechanical strength, and additionally has certain antibacterial properties, which can broaden the use scenarios of the polyester film and extend its service life in harsh environments such as outdoor environments.
[0054] From the comparison of the performance test results of Example 1, Comparative Example 1 and Comparative Example 2, it can be seen that in the process of preparing modified serpentine, saturated fatty acids are necessary components for its synthesis, and calcination in an oxygen atmosphere to form copper oxide from copper formate is a necessary step for its synthesis, which has a certain influence on the performance of the matte polyester film finally prepared.
[0055] By comparing the performance test results of Example 1 and Comparative Example 3, it can be seen that adding the first filler to the black light-absorbing layer and the white surface layer can significantly reduce the light transmittance of the polyester film and improve its mechanical strength. In addition, it can also obtain certain antibacterial properties, thereby increasing the service life of the polyester film.
[0056] Analysis of the performance test results of Example 1 and Comparative Example 4 shows that the effect of using modified serpentine in the first filler is better than that of unmodified serpentine, which can further reduce the light transmittance and improve the mechanical properties of the film.
[0057] In summary, the present application prepares a matte polyester film, and adding a first filler to the black light-absorbing layer and the white surface layer helps to significantly reduce the light transmittance of the polyester film, thereby producing a low-transmittance matte polyester film. In addition, the first filler also makes the polyester film have certain antibacterial properties, which can broaden the application areas of the polyester film, such as making it safer to use in food, hospitals, biology and other fields.
[0058] The above describes the basic principles, main features and advantages of the present application. Those skilled in the art should understand that the present application is not limited by the above embodiments, and the above embodiments and the specification only describe the principles of the present application. The present application may have various changes and improvements without departing from the spirit and scope of the present application, and these changes and improvements fall within the scope of the present application for which protection is sought. The scope of protection claimed by the present application is defined by the attached claims and their equivalents.
Claims
1. A matte polyester film, characterized in that: It comprises two white surface layers, an upper layer and a lower layer, and a black light absorbing layer arranged between the white surface layers. The raw materials for preparing the black light absorbing layer comprise a first filler, and the first filler is a mixture of modified serpentine and polyethylene terephthalate.
2. The matte polyester film according to claim 1, characterized in that: The modified serpentine and the polyethylene terephthalate are mixed in a mass ratio of (1:1) to (1:5) to obtain the first filler.
3. The matte polyester film according to claim 1, characterized in that: The particle size of the modified serpentine is 100-200 nm, and the particle size of the polyethylene terephthalate is 400-500 nm.
4. The matte polyester film according to claim 1, characterized in that: The raw materials for preparing the modified serpentine include: copper formate, serpentine, saturated fatty acid, silane coupling agent and solution.
5. The matte polyester film according to claim 4, characterized in that: The preparation method of the modified serpentine is as follows: dissolving copper formate and adding serpentine powder and saturated fatty acid, reacting at elevated temperature and pressure, then concentrating the solution under reduced pressure to obtain a reactant, calcining the reactant in an oxygen atmosphere and a vacuum atmosphere in turn, grinding the reactant into powder and mixing it with ethanol, then adding a silane coupling agent to react for a period of time, concentrating under reduced pressure and drying to obtain the modified serpentine.
6. The matte polyester film according to claim 1, characterized in that: The raw materials for preparing the black light-absorbing layer also include: black pigment, kaolin, barium sulfate, silane coupling agent and PET masterbatch.
7. The matte polyester film according to claim 1, characterized in that: The raw materials for preparing the white surface layer include: polyacrylonitrile, glass fiber, lignin, the first filler, talcum powder, calcium carbonate, alumina ceramic powder and PET masterbatch.
8. A method for preparing a matte polyester film, characterized in that: The method comprises the following preparation steps: S1: dissolving copper formate and adding serpentine powder and saturated fatty acid, reacting at elevated temperature and pressure, then concentrating the solution under reduced pressure to obtain a reactant, calcining the reactant in an oxygen atmosphere and a vacuum atmosphere in turn, grinding the reactant into powder and mixing it with ethanol, then adding a silane coupling agent to react for a period of time, concentrating under reduced pressure and drying to obtain a modified serpentine; S2: Grinding the modified serpentine and polyethylene terephthalate into powders respectively and mixing them to prepare a first filler; mixing the first filler, black pigment, kaolin, barium sulfate, silane coupling agent and PET masterbatch and extruding the mixture through a twin-screw extruder to obtain a black light-absorbing layer; S3: Grind polyacrylonitrile, glass fiber, and lignin into powder, add the first filler, talcum powder, calcium carbonate powder, alumina ceramics, and PET masterbatch, mix, and extrude through a twin-screw extruder to obtain a white surface layer; The white surface layer is arranged on both sides of the black light-absorbing layer, and the three-layer film is heated, melted and extruded in a casting machine, and the matte polyester film is obtained after stretching and shaping.
9. The preparation method according to claim 8, characterized in that: In the step S1, the reactant is calcined at 600-630° C. for 2-3 h in an oxygen atmosphere, and then transferred to a vacuum furnace and calcined at 850-880° C. for 50-80 min to obtain a calcined product.
10. The preparation method according to claim 9, characterized in that: The calcined product is mixed with ethanol in a mass ratio of 2:(55-59).
Citation Information
Patent Citations
Wear-resistant and corrosion-resistant coating for chemical pump
CN106366913A
High temperature-resistant polyester film and preparation method thereof
CN109054311A
Antibacterial barrier BOPET film and preparation method thereof
CN111703160A
BOPET (Biaxially Oriented Polyethylene Terephthalate) film as automobile bottom film and production process thereof
CN116278293A
High-barrier antibacterial BOPET (Biaxially Oriented Polyethylene Terephthalate) film with slow release performance and preparation method thereof
CN117400613A